PERSPEKTIF HUKUM ISLAM TENTANG DUI PAPPENRE STUDI KASUS DIKELURAHAN NIPAH PANJANG 1 KECAMATAN NIPAH PANJANG KABUPATEN TANJUNG JABUNG TIMUR PROVINSI JAMBI - Gunawan Gunawan; Amir Amir (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2024)
The people of the Nipah Panjang 1 village in a marriage still preserve a custom, one of which is the practice of dui pappenre. this is the most basic requirement that must be met by the prospective husband's family in marriage. For a man, dui pappenre is something that must be prepared to propose to a girl who is of the Bugis tribe in nipah panjang 1. The practice of dui pappenre is an amount of money that must be given by the man to the family of the woman he wants to marry. Which amounts to tens to hundreds of millions of rupiah, this dui papendre is intended as funds for holding wedding receptions or walimatul urs at a woman's residence, which in determining the amount of dui pappenre to be given, everything depends on the agreement of both parties which is usually by looking at social status , education and the economy of the woman and the ability of the man and According to the perspective of Islamic law, the law of dui pappenre, even though there are no provisions in the Shari'a, is still permissible because there is no element of coercion, but on the basis of willingness and consent.